Genetics and Pathophysiology of Primary Dystonia with Special Emphasis on DYT1 and DYT5 - Segawa, Masaya; Nomura, Yoshiko (Seminars in Neurology, 2014)
DYT1 and DYT5 are early-onset dominant inherited dystonias. DYT1 is caused by mutations of the TOR1A gene, located on 9q34, which causes dysfunction of the D1 direct pathway or the indirect pathway. Dysfunction of the former causes postural-type and segmental dystonia; the latter causes action-type dystonia. In families with action-type dystonia, there are cases with focal and segmental dystonia. Ages of onset of postural-type dystonia are around 6 years, and 8 to 10 years in cases of action-type dystonia. Focal and segmental dystonia develops in the teens. Mental and psychological functions are preserved. DYT5 is caused by heterozygous mutations of the GCH1 gene, located on 14q22.1-q22.2. Again, mental and psychological functions are preserved. Clinically, there are two types: postural and action. Postural-type dystonia occurs around 6 years of age, with postural dystonia of one leg, and all extremities and trunk muscles are involved by the late teens. Action-type dystonia shows dystonic movements from around 8 to 10 years of age. In both types, all symptoms show diurnal fluctuations that diminish with age and are no longer apparent in the late teens. L-dopa produces dramatic effects, which continue throughout the course of the illness. In both postural and action types, each family or sporadic case has a particular mutation. It remains unclear why specific mutations cause certain age- and gender-specific symptoms.
Keywords: DYT1; DYT5; Dopa-Responsive dystonia; Segawa disease; postural-type dystonia; action-type dystonia